Integration of Agile Technologies in Internal Audit - Shaikan, Andrii; Hushko, Serhii; Nieizviestna Оlenа (Buhalterinės apskaitos teorija ir praktika, 2024)
The study is devoted to the processes of integration of Agile technologies in internal audits. It was determined that Agile is a method and a way of thinking simultaneously, which ensures timeliness of receiving information, quick response to risks, and acceleration of audit cycles, thanks to which the effect of value creation is achieved for both top management and stakeholders. The analysis of statistical studies of the implementation of Agile technologies allowed the authors to conclude that the Agile approach is increasingly used in enterprises to achieve planned results, and to single out key changes in the concepts of internal audit, which became possible thanks to the implementation of the Agile approach. It is noted that there is no single path for transitioning to the use of Agile methodology for all organisations. In addition, such a transition can cause difficulties associated with rethinking the audit process. That is why the authors attempted to unify the work cycles of the internal Agile audit.